Project Based Learning pada Literasi Sains Berbasis Budaya Lokal Bahari dengan Penggunaan Alat Wind Detection - Eka Candra Kahiking (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
The natural phenomenon of the sea about the wind that is still not taken up in science learning and learning media is needed. To understand the phenomenon, scientific literacy is needed, it is necessary for the creativity of the teacher. The aim is to improve students' scientific literacy skills and obtain teaching aids that can be used in local maritime and 21st-century culture-based learning. Learning activities are carried out using a project-based learning model combined with scientific literacy stages using a Bluetooth digital wind detection tool. learning media is developed and validated by experts, learning stages are developed according to needs, scientific literacy skills are obtained based on observations of scientific literacy skills, interviews, response questionnaires, and product assessments at 80 to 100%, are in the good and very good categories. It is concluded that this learning innovation can improve students' scientific literacy skills, and produce teaching aids that utilize local culture based technology according to the demands of the 21st century learning that can be used in science learning in everyday life to help the community.